Chapter 12 The usefulness of violent ends : apocalyptic imaginaries in the reconstruction of society - van den Heever, Gerhard (Taylor & Francis, 2018)
Throughout 2015 and 2016 there have been constant violent protests, destruction of university property, and clashes between protesters and police and security personnel on various campuses. An apocalyptic worldview is essentially a violent worldview. In the eschatological lore that animates ISIS ideologically, the city of Dabiq in northern Syria near the Turkish border is the site of the end-time apocalyptic war. In the vision of the author of the Dabiq article, immersion in Western society is to be a hypocrite or an about-to-be apostate. The changes in social constitution of Spanish society also brought with them increasing clamour for a political voice. As the Republican government set about its programme of re-engineering Spanish society, to a large extent the Catholic Church became the central focus of the cultural wars escalating in the country. Two political forces played a central role in the unfolding of the civil war: the army and the Catholic Church.
Australian Research Council
English
Keywords: Ancient history: to c 500 CE; Religious conflict in the ancient world|Religious persecution in the ancient world|Religious conflict in late antiquity|Religious persecution in late antiquity|Religious violence in late antiquity|Religious violence in the ancient world|Iconoclasm in the ancient world|Iconoclasm in the late antiquity|The Funerary Speech for John Chrysostom|John of Ephesus$1 (Bs Church History|Disability and early christianity|Deformity and early christianity|Religious persecution and early christianity|Religious violence and early christianity|Religious conflict and early christianity|pseudo-Clementine Homilies|Religious Violence in Late Antique Egypt|destruction of the Serapeum at Alexandria|Abbot Shenoute|Closure of temple of Isis Philae|Panopolis|Cologne Mani Codex|Manichaean Kephalaia|Gnostic-Manichaean Christianity|Hagiasma of Chonai|Jan Bremmer|Pieter J. J. Botha|Chris L. de Wet|Christine Shepardson|Alan H. Cadwallader|Christoph Stenschke|Maijastina Kahlos|Jitse H. F. Dijkstra|Peter Van Nuffelen|Elizabeth DePalma Digeser|Gerhard van den Heevers